Importância do diagnóstico e tratamento da fenilcetonúria Diagnoses and treatment of phenylketonuria - Nádia VM de Mira; Ursula M Lanfer Marquez (Universidade de São Paulo, 2000)
A fenilcetonúria (PKU) é o mais comum dos erros congênitos do metabolismo de aminoácidos. Resulta da deficiência da fenilalanina hidroxilase, enzima que catalisa a conversão de fenilalanina em tirosina. A introdução de uma dieta com baixo teor de fenilalanina deve ter início nos primeiros meses de vida, de preferência no primeiro mês, para evitar o retardo mental, manifestação clínica mais severa da doença. Foi elaborada revisão sobre essa temática, que aborda desde a PKU clássica até a hiperfenilalaninemia branda, incluindo relato sobre a PKU maternal e os efeitos da exposição do útero a altos níveis de fenilalanina sobre o feto. Phenylketonuria is the most common inborn error of amino acid metabolism. It is due to a deficiency of phenylalanine hydroxylase, which normally converts phenylalanine to tyrosine. A diet low in phenylalanine starting in the first month of life can significantly reduce mental retardation, the most important feature of the disease. The aim of the review is to discuss the difficulties found in the diagnosis of PKU and its variants, ranging from classic phenylketonuria to mild hyperphenylalaninaemia, and the effects of dietary restriction of phenylalanine on the growth and development of children. Also, we present the current controversies about the age of discontinuing the dietary treatment. This review summarizes the benefits and problems emerging from a prolonged therapy taking into account dietary compliance in different age groups, and discusses dietary alternatives to the synthetic amino acid mixtures free of phenylalanine, based on low phenylalanine protein hydrolysates. In addition, we show some information about the effects of maternal phenylketonuria on pregnancy outcome and infant development, if exposed to high phenylalanine levels intra uterineo.